Spatially and temporally resolved spectro-electrochemical analysis of electrochromic WO3 electrodes - Darmawi, Sabrina; Justus Liebig University Giessen (My University, 2015)
An experimental setup is presented, which provides the opportunity to perform optical transmission analysis during electrochemical ion insertion into electrochromic materials, such as WO3, with a time resolution on the second scale and local information on the micrometer scale. To conduct the experiments, WO3 thin film electrodes were synthesized by various methods and lithographically micro structured. WO3 was analyzed with respect of two main types of electrochemical experiments: (1) time resolved in situ transmission experiments during electrochemical ion insertion/extraction and (2) spatially and time resolved transmission experiments for the visualization and quantification of diffusion in WO3.(1) The correlation between the oxidation states of tungsten and the coloration efficiency of nanocrystalline WO3 was analyzed and a two-step mechanism for the coloration process is proposed. For this the lithium inserted WO3 electrodes were additionally investigated by XRD and XPS. During coloration tungsten is electrochemically reduced, and the formation of W5+ was found in the first step. However, only the formation of W4+, which takes place in the second step (at lower electrode potentials), comes along with the main coloration. XRD results show that after the formation of W4+, LixWO3 exhibits a cubic crystal structure instead of the initial tetragonal structure.(2) By patterning a transparent layer deposited on top of the WO3 thin film, local insertion of hydrogen into the thin film could be achieved and ion transport in the plane of the WO3 film could be visualized. The obtained temporal and spatial dependence of the observed coloration of WO3 was described by a simple 1D diffusion model. A diffusion coefficient for hydrogen in amorphous WO3 thin films was determined with a value of D = 1.3E(-10) cm^2/s.

Es wird ein experimenteller Aufbau vorgestellt, welcher Transmissionsuntersuchungen während elektrochemischer Ioneninsertion in elektrochrome Materialien, wie WO3, mit einer Zeitauflösung im Sekunden-Bereich und einer Ortsauflösung im Mikrometer-Bereich zulässt. Um die Experimente durchführen zu können, wurden WO3 Dünnfilmelektroden mittels verschiedener Methoden hergestellt und lithografisch mikrostrukturiert. Diese Dünnfilm-Elektroden wurden in Hinblick auf zwei Hauptexperimente untersucht: (1) zeitaufgelöste in situ Transmissionsexperimente während Ioneninsertion bzw. -extraktion und (2) orts- und zeitaufgelöste Transmissionsexperimente für die Visualisierung und Quantifizierung der Diffusion in WO3.(1) Die Korrelation zwischen den Oxidationszuständen von Wolfram und der Verfärbungseffizienz von nanokristallinem WO3 wurde untersucht und ergab, dass der Verfärbungsprozess einem zweistufigem Mechanismus unterliegt. Dazu wurden die insertierten WO3 Proben zusätzlich mittels XRD und XPS untersucht. Während der Verfärbung wird Wolfram W6+ elektrochemisch reduziert und die Bildung von W5+ konnte der ersten Stufe zugeordnet werden. Jedoch trägt die Bildung von W4+, welches während der zweiten Stufe beobachtet wird (bei niedrigeren Elektrodenpotenzialen), zur Hauptverfärbung von WO3 bei. XRD Messungen ergaben zudem, dass LixWO3 nach der Bildung von W4+ eine kubische statt der ursprünglichen tetragonalen Struktur aufzeigt.(2) Durch das Strukturieren einer durchsichtigen, auf dem WO3 Dünnfilm aufgebrachten, teilweise ionenblockierende Schicht konnte der Ionentranport der insertierten Spezies in der Ebene des Dünnfilms visualisiert werden. Die somit ermittelte zeit- und ortsabhängige Verfärbung von WO3 wurde mit einem einfachen 1D Modell beschrieben. Und es wurde ein Diffusionskoeffizient von Wasserstoff in amorphem WO3 von D = 1.3E(-10) cm^2/s ermittelt.
Orts- und zeitaufgelöste spektro-elektrochemische Messungen an WO3 Elektroden
Keywords: ddc:530